"Zeleno na pot" - Mežek, Lucija (Pravni letopis, 2025)
The article examines greenwashing in the tourism industry and its legal, marketing, and social implications. It focuses on examples from air and cruise transport, travel packages, and cycling tourism, where companies use environmental claims without adequate evidence, thereby misleading consumers. The paper analyses the European and Slovenian legal frameworks, which are gradually tightening or prohibiting vague and deceptive environmental statements. The central part of the article is devoted to tourism transport, where greenwashing is most common—particularly in aviation, cruise travel, and package tours. It describes cases of companies such as KLM and Ryanair, which mislead consumers through advertising “sustainable fuels” or “carbon neutrality.” The article also presents court proceedings and the reactions of EU institutions. It is written both to raise awareness among average consumers and to warn tourism operators who engage in such practices, while calling for greater transparency and accountability in the advertising of sustainable travel.
Keywords: advertising; air transport; consumers; environmental claims; greenwashing; Ladijski potniki; Letalski potniki; letalski promet; oglaševanje; okoljske trditve; potrošniki; sustainable development; tourism; trajnostni razvoj; travel packages; turistični paketi; turizem; Varstvo okolja; Varstvo potrošnikov; zeleno zavajanje